PERTUMBUHAN TANAMAN BUAH NAGA MERAH (Hylocerus polyrhizus) PADA BERBAGAI KONSENTRASI BENZILAMINO PURINE DAN UMUR KECAMBAH SECARA IN VITRO - Wahyuni, Fadlia; Basri, Zainuddin; Bustami, Mirni Ulfa (AGROTEKBIS, 2013)
Dragon fruit plants at beginning used as an ornamental plant because of its unique figure, exotic, as well as flowers and fruit look very beutiful. However, constrain encountered in the development of these plants is the availability of seedlingin large numbers with shorten time. To solve this problem, it can be done through tissue culture. This research was conducted at the Laboratory of Plant Biotechnology Faculty of Agriculture, University of Tadulako Palu, from August to October 2012. The purpose of this study was to determine the growth of dragon fruit plants at various ages germination and BAP concentrations in vitro. This study used a design Plots Separated ( RPT ) with treatment in the main plot was the age of germination 3, 4, 5 week after trasplanting, while the subplot treatment was the concentration of BAP: 1, 2, 3 ppm. Therefore, there are 9 combinations of treatment and repeated four times, so there are 36 experimental units. Each unit used three explants, so there are 108 explants were used. The results showed that germination ageeffectsignificant on plant height and number of shoots, while the concentration of BAP significantly effect on the number of shoots and number of roots. Media added with 2 ppm BAP (B2) average plant height 3.37, number of shoots 4.08per explant respectively, and media added with 1 ppm BAP (B1) Average number of roots per explant wasÂ 0.53.